2022
DOI: 10.1177/03635465211065446
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Coracoid, Distal Clavicle, and Scapular Spine for Autograft Augmentation of Glenoid Bone Loss: A Radiologic and Cadaveric Assessment

Abstract: Background: Glenohumeral instability caused by bone loss requires adequate bony restoration for successful surgical stabilization. Coracoid transfer has been the gold standard bone graft; however, it has high complication rates. Alternative autologous free bone grafts, which include the distal clavicle and scapular spine, have been suggested. Study Design: Controlled laboratory study. Purpose: The purpose of this study was to determine the percentage of glenoid bone loss (GBL) restored via coracoid, distal cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 49 publications
0
11
1
Order By: Relevance
“…29 Therefore, the ability for glenoid restoration of the scapular spine is worth investigating. Rodriguez et al 36 found that the scapular spine was capable of achieving 28.2% glenoid restoration on average, compared with 31% in our results. The difference might be attributed to the different graft lengths harvested in the study.…”
Section: Discussioncontrasting
confidence: 45%
“…29 Therefore, the ability for glenoid restoration of the scapular spine is worth investigating. Rodriguez et al 36 found that the scapular spine was capable of achieving 28.2% glenoid restoration on average, compared with 31% in our results. The difference might be attributed to the different graft lengths harvested in the study.…”
Section: Discussioncontrasting
confidence: 45%
“…There are limitations to the thickness of the graft that can be acquired given the depth of the scapular spine, therefore the amount of glenoid bone loss should be considered. With that said, studies have suggested that up to an average of 26% of glenoid bone loss can be adequately treated with scapular spine autograft [ 3 ]. Scapular spine autograft for glenoid bone loss should be considered as an option alongside other treatments for glenoid bone loss after adequate assessment of percent bone loss.…”
Section: Discussionmentioning
confidence: 99%
“…Optimal treatment for these patients with significant bone loss remains a topic of discussion with a wide array of autograft and allograft techniques utilized for glenoid augmentation. The Latarjet procedure, using coracoid autografts, is perhaps most commonly used to restore glenoid bone loss; however, high complication rates of coracoid grafts have urged the exploration of other graft options [3]. Several studies have identified scapular spine autograft to be suitable for restoring glenohumeral stability from bone quality and biomechanical standpoints; however, there are few reports on the indications and details of this procedure [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Recent work has shown that the DCA can reliably restore up to 30% glenoid bone loss. 41 However, a different study showed that DCA was able to reconstruct 22% of the glenoid face. 42…”
Section: Types Of Free Bone Graftsmentioning
confidence: 99%
“…First, the scapular spine graft only seems to be suitable for reconstruction of relatively small glenoid bone defects because a study showed that only 66% of scapular spine grafts were able to restore a 20% glenoid bone loss defect. 41 Furthermore, the scapular spine significantly narrows from the posterior crest toward the supraspinatus fossa, drawing concern for potential bony fracture during screw placement (Figure 5). 41 Second, this graft does not contain cartilage because it is nonarticular.…”
Section: Types Of Free Bone Graftsmentioning
confidence: 99%